Choice of the method of surgical treatment for ectasias of saphenofemoral and saphenopopliteal junctions - O. V. Sokolov (Клінічна хірургія, 2019)
Objective. Analysis of results of radiofrequency laser ablation and crossectomy with stripping in patients, suffering varicose disease of the lower extremities veins in ectasias, sizing more than 14 mm in saphenofemoral and saphenopopliteal junctions.